BODY IMAGE IN PRISON: PERCEPTIONS OF IMPRISONED WOMEN - Ana Luísa Canário Carlos de Andrade; Ana Paula Dias Inocêncio Barbosa; Ursula Viana Bagni (Universidade do Estado do Rio de Janeiro, 2018)
Objective: To evaluate the perception of body image among imprisoned women in relation to the current body size, body before imprisonment, and the ideal body. Methodology: A cross-sectional study carried out with 149 female prisoners from Natal, State of Rio Brande do Norte, Brazil. The perception of body image was assessed using a figure rating scale validated for Brazilian people, containing 15 silhouette figures and their respective values of body mass index. Each participant indicated the figure reflecting her current body size (at the time of the interview), her body before incarceration, and the body she would like to have. The analysis of the concept of ideal body and the perception of changes in their bodies after imprisonment was performed using the chi- square test, considering p-value <0.05 for statistical significance. Results and discussion: Half of prisoners perceived themselves to be obese (50.3%) or overweight (26.8%). Regarding the desired body, 83.8% would like to be overweight, and 40% of obese women want to maintain their body size or even increase it. Thus, it was found that body image and ideal body in prison environment are very complex issues, going beyond the slim beautiful body traditionally desired by most women. Conclusion: The high proportion of female convicts who are overweight and who yearn for even more robust bodies points to the need to intensify health actions; further research within the scope of Social and Human Sciences; as well as qualified healthcare professionals to work in these institutions. DOI: 10.12957/demetra.2018.33309